A Multi-Objective optimization framework for the sustainable machining of Monel 400 - Binayak Sen; Prasadaraju Kantheti; Sachin Rathore; Bhavesh Kanabar; Ramachandran Thulasiram; Manoj Kumar; Abhijit Bhowmik; A. Johnson Santhosh (Scientific Reports)
Abstract This study explores the synergistic effects of lubrication as well as cooling on the machinability behaviour of the superalloy Monel 400. A comparative assessment was conducted across four machining environments—dry cutting, Minimum Quantity Lubrication (MQL), Cryogenic CO₂, and a hybrid MQL + CO₂ approach. Among these, MQL + CO₂ exhibited superior performance, yielding reductions of 19.58% in cutting force, 19.10% in tool wear, and 47.19% in surface roughness relative to dry cutting. Scanning Electron Microscopy (SEM) analysis identified adhesion and abrasion as the predominant wear mechanisms. Adhesion, driven by elevated cutting temperatures, facilitates material transfer between the tool and workpiece, while abrasion arises from the interaction of hard alloy particles with the tool surface, resulting in micro-scratches. Analysis of variance revealed that feed and cutting speed are the utmost influential parameters influencing machining outcomes. Utilizing Multi-Objective Response Surface Methodology, the study established optimal machining conditions—cutting speed of 78.35 m/min, feed of 0.1 mm/rev, and depth of cut of 1 mm—attaining a composite desirability of 0.84. These findings offer a sustainable framework for optimizing the machinability of Monel 400, with significant implications for aerospace and high-precision manufacturing industries.